Zinc Finger Proteins in Head and Neck Squamous Cell Carcinomas: ZNF540 May Serve as a Biomarker - Joanna Sobocińska; Joanna Nowakowska; Sara Molenda; Anna Olechnowicz; Kacper Guglas; Joanna Kozłowska-Masłoń; Urszula Kazimierczak; Marta Machnik; Urszula Oleksiewicz; Anna Teresiak; Katarzyna Lamperska; Tomasz Kolenda (Current Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is one of the ten most common cancers. Most cancer cases originate from alcohol and tobacco consumption. However, studies have demonstrated that human papillomavirus (HPV) infection, particularly HPV-16, may also significantly influence disease progression. The KRAB-ZNF family of genes is involved in epigenetic suppression, and its involvement in carcinogenesis is the subject of extensive studies. The available literature data demonstrate that they may play different roles, both as tumor suppressors and oncogenes. In this study, six ZNF genes, ZFP28, ZNF132, ZNF418, ZNF426, ZNF540, and ZNF880, were tested using several in silico approaches based on the TCGA and GEO datasets. Our analyses indicate that the expression of the analyzed ZNFs was significantly downregulated in tumor tissues and depended on tumor localization. The expression levels of ZNFs differed between HPV-positive vs. HPV-negative patients depending on the clinical-pathological parameters. More specifically, the patients with higher levels of ZNF418 and ZNF540 showed better survival rates than those with a lower expression. In addition, the level of ZNF540 expression in HPV-positive (HPV(+)) patients was higher than in HPV-negative (HPV(−)) patients (p < 0.0001) and was associated with better overall survival (OS). In conclusion, we demonstrate that ZNF540 expression highly correlates with HPV infection, which renders ZNF540 a potential biomarker for HNSCC prognosis and treatment.